Validation of NOViSE – a novel Natural Orifice Virtual Surgery Simulator - Korzeniowski,P; Brown,DC; Sodergren,M; Barrow,A; Bello,F (Surgical Innovation, 2016)
The goal of this study was to establish face, content and construct validity of NOViSE – the first force-feedback enabled virtual reality (VR) simulator for Natural Orifice Transluminal Endoscopic Surgery (NOTES). Fourteen surgeons and surgical trainees performed three simulated hybrid trans-gastric cholecystectomies using a flexible endoscope on NOViSE. Four of them were classified as “NOTES experts” who had independently performed ten or more animal or human NOTES procedures. Seven participants were classified as ‘Novices’ and three as ‘Gastroenterologists’ with no or minimal NOTES experience. A standardized five-point Likert-scale questionnaire was administered to assess the face and content validity. NOViSE showed good overall face and content validity. In 14 out of 15 statements pertaining to face validity (graphical appearance, endoscope and tissue behaviour, overall realism), ≥50% of responses were “agree” or “strongly agree”. In terms of content validity, 85.7% of participants agreed or strongly agreed that NOViSE is a useful training tool for NOTES and 71.4% that they would recommend it to others. Construct validity was established by comparing a number of performance metrics such as task completion times, path lengths, applied forces, etc. NOViSE demonstrated early signs of construct validity. Experts were faster and used a shorter endoscopic path length than novices in all but one task. The results indicate that NOViSE authentically recreates a trans-gastric hybrid cholecystectomy and sets promising foundations for the further development of a VR training curriculum for NOTES without compromising patient safety or requiring expensive animal facilities.